(3eNJUQ GdeYJeO aj CUhd Gdabgs - (3SdjeGf Hf fGUQ Hf SYjOs; (3eMeO Hf Ydj GdWjH GdHUQj, CHh GdMSjf,J (B436 (3g` s ((3eMeO Hf fGUQ Hf SYjO Hf YHO Gddg s)
(3ChdgG (B:s
(3JcQje MGWce Gddg HYdeg Cfce CWddJe Ydi cJGH GdeYJeO ai CUhd Gdabg s
(3BNQgG (B:s
(3dcGf MGUdkG acGf jhLO YfO GdWdH s
(3fSNI KGfjI ecQQI ef Qbe (B129 (3CUhd abg (B" (3GdLRA GdChd(B"s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs